2018
DOI: 10.5128/erya14.15
|View full text |Cite
|
Sign up to set email alerts
|

The perceived effectiveness of written peer feedback comments within L2 English academic writing courses

Abstract: Abstract.At one Estonian university, we have designed a course to support the writing skills of doctorate students who need to write scientific articles for publication in their L2 English. We provide this support by placing these students into small discipline-specific writing groups where they periodically give and receive written feedback on their draft articles. Knowing what may constitute an effective feedback comment will enable us to improve upon current pedagogical practices. In this study, we develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This study has determined that authors use a similar amount of social presence within their CLs (contained within 43% of TUs). Researchers have shown that students as both reviewers and feedback recipients both use and value affective language in written peer feedback comments (Cho, Schunn, and Charney 2006, Gee 1972, Yallop and Leijen 2018, and this perception seems to also hold true regarding authors as self-assessment providers. Furthermore, and within a sociocultural framework, studies show that high social presence within communities of inquiry can promote cognitive presence by developing a sense of community (Cahusac de Caux et al 2017, Garrison, Anderson andArcher 1999).…”
Section: Tus By 'Social Presence'mentioning
confidence: 97%
See 4 more Smart Citations
“…This study has determined that authors use a similar amount of social presence within their CLs (contained within 43% of TUs). Researchers have shown that students as both reviewers and feedback recipients both use and value affective language in written peer feedback comments (Cho, Schunn, and Charney 2006, Gee 1972, Yallop and Leijen 2018, and this perception seems to also hold true regarding authors as self-assessment providers. Furthermore, and within a sociocultural framework, studies show that high social presence within communities of inquiry can promote cognitive presence by developing a sense of community (Cahusac de Caux et al 2017, Garrison, Anderson andArcher 1999).…”
Section: Tus By 'Social Presence'mentioning
confidence: 97%
“…Thus, a useful CL should help reviewers write useful feedback comments, and useful feedback comments are likely to exert a positive affect and/or a positive effect on the author's revision process. However, and apart from studies conducted by the authors (Yallop, 2016;Yallop, 2017;Yallop & Leijen, 2018;Yallop, Taremaa & Leijen, in press), there seems to be little research into how CLs can be used to generate useful written feedback comments in tandem with, or instead of, rubrics within the peer feedback process within any educational context.…”
Section: All the Best Participantmentioning
confidence: 99%
See 3 more Smart Citations